2019
DOI: 10.1002/mds.27770
|View full text |Cite
|
Sign up to set email alerts
|

SNCAandmTORPathway Single Nucleotide Polymorphisms Interact to Modulate the Age at Onset of Parkinson's Disease

Abstract: Background Single nucleotide polymorphisms (SNPs) in the α‐synuclein (SNCA) gene are associated with differential risk and age at onset (AAO) of both idiopathic and Leucine‐rich repeat kinase 2 (LRRK2)‐associated Parkinson's disease (PD). Yet potential combinatory or synergistic effects among several modulatory SNPs for PD risk or AAO remain largely underexplored. Objectives The mechanistic target of rapamycin (mTOR) signaling pathway is functionally impaired in PD. Here we explored whether SNPs in the mTOR pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 56 publications
2
23
0
Order By: Relevance
“…Genome-wide association studies have demonstrated association between SNCA common variants and susceptibility to sporadic PD disease ( 54 ). In line with our findings, a recent meta-analysis showed that rs356219 is associated with increased risk of PD ( 55 ) (see ref in the comment field), while a recent study found that SNCA can modulate the PD age at onset ( 56 ).…”
Section: Discussionsupporting
confidence: 91%
“…Genome-wide association studies have demonstrated association between SNCA common variants and susceptibility to sporadic PD disease ( 54 ). In line with our findings, a recent meta-analysis showed that rs356219 is associated with increased risk of PD ( 55 ) (see ref in the comment field), while a recent study found that SNCA can modulate the PD age at onset ( 56 ).…”
Section: Discussionsupporting
confidence: 91%
“…A variant in RPS6KA2 was recently shown to be in an three-way epistatic relationship with a variant in SNCA and a variant in RPTOR in an age at PD onset study. 67 However, this admixture peak did not achieve significance in the joint test nor was the fine-mapped variant regionally significant ( see methods ). The mean proportion of African ancestry in LARGE-PD was under 0.06, meaning that we were underpowered to detect African-specific variation.…”
Section: Discussionmentioning
confidence: 99%
“…6). Although the mechanistic link between αSyn and mTORC1 remains to be established, recent evidence shows that genetic variability in the mTOR pathway contributes to SNCA effects in disease pathogenesis [79].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a quantitative proteomics study of a pre-symptomatic p.A53T-αSyn Drosophila model shows significant upregulation of ribosomal proteins in the p.A53T flies (71). Although the mechanistic link between p.A53T-αSyn and mTORC1 remains to be established, recent evidence shows that genetic variability in the mTOR pathway contributes to SNCA effects in disease pathogenesis (72).…”
Section: Discussionmentioning
confidence: 99%